ChemInform Abstract: New ent‐Abietane and ent‐Kaurane Diterpenoids from Isodon rubescens. Issue 26 (6th June 2013) - Sun, Han‐Dong; et al., et al.
Abstract isolation, structure elucidation and cytotoxicity of ent‐abierubesins A—E (I)—(IV) and new ent‐kauranoids, hubeirubesins A (V) and B (VI)